The Effect of Work-Life Balance and Perception of Compensation on Job Satisfaction Among Married Employees - Hikmatunnazilah Hikmatunnazilah; Indah Mulyani; Siti Marliah Tambunan; Dona Eka Putri (Green Publisher Indonesia, 2026)
An employee is a supporting factor that is quite calculated in a company. It is not uncommon for married employees to still actively work in the company. The purpose of this study was to determine whether there is an influence between work life balance and perception of compensation on job satisfaction of married employees. The method used is quantitative research method. Respondents in this study were 143 married employees. The data collection technique used purposive sampling. The distribution of questionnaire items using google forms. Work life balance is measured using a scale compiled and adapted from Hayman, consisting of 15 statement items. Perception of compensation is based on a scale from Nyberg, A, consisting of 3 statement items, and job satisfaction is measured using a scale compiled and adapted by Macdonald and Maclntyre, consisting of 10 statement items. The results of this study show that the hypothesis is accepted, namely the influence between work life balance and perception of compensation on job satisfaction in married employees. The results of hypothesis testing show a significance value of 0.000 (p <0.05) and an R square value of 0.162, which means that the effect of work life balance and perception of compensation simultaneously affects job satisfaction by 16.2% and the rest is influenced by other variables outside the study. Based on the results of the empirical mean calculation